Leisure, work, and family: How IronMEN balance the demands of three resource-intensive roles. (26th May 2016) - Simmons, Jason M.; Mahoney, Tara Q.; Hambrick, Marion E.
ABSTRACT: Building on the work of Hambrick, Simmons, and Mahoney (2013 ), the purpose of this study was to examine perceptions of leisure-work-family conflict among male Ironman participants, as well as the strategies and support mechanisms used to help manage their various role demands. Semi-structured interviews were conducted with 11 males who successfully completed at least one Ironman event. For these males, perceptions of inter-role conflict were minimal, despite the presence of similar demands reported in the Hambrick et al. study. Participants still emphasized the need for family and work role support, as well as specific role management strategies, namely scheduling, sacrifice, and role prioritization, to make their Ironman aspirations a reality. The impact of gender roles on perceptions of leisure-work-family conflict is also discussed.